When Teaching is Joyfully Subversive: Toward a Holistic Curriculum for Adult and Higher Education - Randee Lipson Lawrence (Adult Education Research Conference, 2014)
This paper describes a participatory, inclusive and holistic curriculum model that adheres to the ideals of adult education while meeting institutional requirements.